Banks and Labor as Stakeholders : Impact on Economic Performance - Ueda, Kenichi; Claessens, Stijn (Washington, D.C. : International Monetary Fund, 2008)
Traditionally, the impacts of the rights of financial institutions and workers on corporate performance have been analyzed independently. Yet, theory clearly indicates that the combination of relative powers of different stakeholders affects a firm overall performance. Using U.S. state level and state-industry level data, we investigate how output growth is affected by bank branch deregulation and employment protection occurring over 1972-1993. We find that financial liberalization positively impact overall state growth but greater workers' rights affects it ambiguously. At the industry level, however, employment protection promotes those industries that are more knowledge intensive, while the effect of financial liberalization does not differ across industries that vary in external financing dependency. The results hold controlling for changes in shareholders' rights, which itself is not significant. The findings suggest that financial liberalization operates mostly through an efficiency channel, better reallocating resources across sectors, while employment protection creates higher incentives and encourages more sector-specific, human capital investments. Overall, the results show that the strength of stakeholders' protection affects performance through efficiency channels and provide support for a stakeholders' view of corporate governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet